Nutrition security and traditional food markets in Africa: gender insights - de Kanter, Emilie; Trevenen-Jones, Ann; Billiard, Charlie M. J. (Frontiers in Sustainability, 2024)
Malnutrition is a major global challenge. Multiple forms, from underweight to obesity, exist, and several forms coexist within communities and households. Traditional food markets, also known as wet, local, or informal markets, are widespread in sub-Saharan Africa (SSA) and are a key place where people buy and sell food and socially interact, especially those vulnerable to malnutrition. As such they are vital to food and nutrition security. While it is recognized that gender is an important consideration in food and nutrition security, very little has been published in peer reviewed journals, with respect to gender and traditional food markets in SSA. This mini review aims to explore the nexus role of traditional food markets and gender in food and nutrition security. This study presents a narrative literature review, informed by literature identified in a systematic manner. Four databases were searched for key terms, including nutrition, different forms of malnutrition, gender, traditional food markets, and vendors. The papers provided insight into two main topics pertaining to the role of traditional food market practices, gender, and food and nutrition security. While few papers were identified in this mini review, they illustrated insightful nuances into traditional food markets, gender, and food and nutrition security. There is a need for explicitly framed gender studies that can better inform the limited existing knowledge of the experiences of gender and nutritional security of women and men in traditional food markets in SSA.